FOOD PROTEIN-INDUCED ENTEROCOLITIS SYNDROME (FPIES) IN A 6-MONTH-OLD INFANT: CASE REPORT AND LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2026)
Food Protein-Induced Enterocolitis Syndrome (FPIES) is a non-immunoglobulin E (IgE)-mediated food allergy that primarily affects infants and may mimic acute infectious gastroenteritis. We report a case of a 6-month-old girl who had been exclusively breastfed and developed repetitive vomiting and profuse watery diarrhea leading to severe dehydration approximately one hour after her first exposure to cow’s milk-based formula. The patient was treated with intravenous fluid resuscitation and switched to an extensively hydrolyzed formula, resulting in rapid clinical improvement. Two weeks later, an oral food challenge performed under medical supervision reproduced the symptoms within 1–2 hours, without cutaneous or respiratory manifestations. The patient fulfilled the 2017 international consensus diagnostic criteria for acute FPIES. This case highlights the diagnostic challenges of FPIES due to its non-specific presentation. It emphasizes the importance of careful dietary history and supervised oral food challenge in confirming the diagnosis. Early recognition and appropriate elimination diet, in accordance with current European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) (2024) and World Allergy Organization (WAO) (2023) recommendations, are essential to optimize outcomes and avoid unnecessary treatments.
Keywords: Food Protein-Induced Enterocolitis Syndrome, FPIES, Non-IgE-mediated food allergy, Cow’s milk allergy, Oral food challenge